Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)=1/2*2/3......*19/20
=1/20
b)=3/2*4/3......*2008/2007
=3/2007
(1-1/2x1/2)x(1-1/3x1/3)x(1-1/4x1/4)x…x(1-1/2007x1/2007) = ( 1 - 1/4 ) x ( 1 - 1/9 ) x ( 1- 1/16) x .....x ( 1 - 1/4028049) = 3/4 x 8/9 x 15/16 x .....x 4028048 / 4028049 = 3 x 8 x 15 x .....x 4028048 / 4 x 9 x 16 x ......x 4028049 = 1 x 3 x 2 x 4 x 3 x 5 x .....x 2006 x 2008 / 2x2 x 3 x3 x 4 x 4 x .....x 2007 x 2007 = ( 1 x 2 x 3 x .....x 2006) x ( 3 x 4 x 5 x .....x 2008) / ( 2 x 3 x 4 x ....x 2007) x ( 2 x 3 x 4 x ....x 2007) = 2008 / 2007 x 2 = 1004 / 2007
(1-1/2x1/2)x(1-1/3x1/3)x(1-1/4x1/4)x…x(1-1/2007x1/2007)
= ( 1 - 1/4 ) x ( 1 - 1/9 ) x ( 1- 1/16) x .....x ( 1 - 1/4028049)
= 3/4 x 8/9 x 15/16 x .....x 4028048 / 4028049
= 3 x 8 x 15 x .....x 4028048 / 4 x 9 x 16 x ......x 4028049
= 1 x 3 x 2 x 4 x 3 x 5 x .....x 2006 x 2008 / 2x2 x 3 x3 x 4 x 4 x .....x 2007 x 2007
= ( 1 x 2 x 3 x .....x 2006) x ( 3 x 4 x 5 x .....x 2008) / ( 2 x 3 x 4 x ....x 2007) x ( 2 x 3 x 4 x ....x 2007)
= 2008 / 2007 x 2
= 1004 / 2007
\(E=\left(1-\frac{1}{2}\right)\left(1-\frac{1}{3}\right)....\left(1-\frac{1}{2006}\right)\left(1-\frac{1}{2007}\right)\)
\(E=\frac{1}{2}.\frac{2}{3}....\frac{2005}{2006}.\frac{2006}{2007}\)
\(E=\frac{1.2.3.4...2005.2006}{2.3.4.5....2006.2007}\)
\(E=\frac{1}{2007}\)
a: \(=\dfrac{\left(\dfrac{1}{2}:\dfrac{1}{2}-\dfrac{1}{4}:\dfrac{1}{4}+\dfrac{1}{8}:\dfrac{1}{8}-\dfrac{1}{10}:\dfrac{1}{10}\right)}{1+2+3+...+2008}\)
=0
c: =8,1*5/3*1875+13,5*625
=13,5(1875+625)
=13,5*2500
=33750
Ta có:\(C=\left(\dfrac{1}{2}-1\right)\times\left(\dfrac{1}{3}-1\right)\times\left(\dfrac{1}{4}-1\right)\times...\times\left(\dfrac{1}{2006}-1\right)\times\left(\dfrac{1}{2007}-1\right)\)
\(=\dfrac{-1}{2}\times\dfrac{-2}{3}\times\dfrac{-3}{4}\times...\times\dfrac{-2005}{2006}\times\dfrac{-2006}{2007}\)
\(=\dfrac{1}{2007}\)
Ta có: \(C=\left(\dfrac{1}{2}-1\right)\left(\dfrac{1}{3}-1\right)\cdot...\cdot\left(\dfrac{1}{2006}-1\right)\left(\dfrac{1}{2007}-1\right)\)
\(=\dfrac{-1}{2}\cdot\dfrac{-2}{3}\cdot\dfrac{-3}{4}\cdot...\cdot\dfrac{-2005}{2006}\cdot\dfrac{-2006}{2007}\)
\(=\dfrac{1}{2007}\)
ta có: ( 1-1/2)x(1-1/3)x(1-1/4)*...*(1-1/2007)
=1/2*2/3*3/4*...*2006/2007
=( 1*2*3*4*5*...*2006)/(1*2*3*4*5*...*2007)
= 1/2007
Vậy kq của phép tính trên là: 1/2007
nhớ tíc mk nhé